Impact DASH System on Patients’ Dietary Pattern after Recovery from Myocardial Infarction - Hadi, Sabri Sh.; Khudur, Khalida M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: One of the top three causes of death and morbidity is cardiovascular disease Myocardial infarction is a clinical illness defined by quickly growing severe myocardial ischemia. It is the most frequent health problem in the world and the main cause of mortality. Objectives: The study aims to assess the dietary pattern of food intake frequency for patients with post- myocardial infarction. Patients & Methods: The quasi-experimental design has been carried out to determine the impact of the Dietary Approaches to Stop Hypertension system on patients with post-myocardial infarction, in the Al-Diwaniyah Teaching Hospital’s cardiac outpatient clinic for the period from 17th April 2023 to 3rd May, 2024. Nonprobability (purposive) sample of (60) patients were selected who recovering from myocardial infarction at AL Diwaniyah Teaching Hospital. The study instrument comprised of (3) parts: part I: demographic details of the patient, which included seven items. Part II: Data on clinical characteristics, consisting of (3) items and Part III: Evaluation of diet frequency consisting of (8) items. Results: The study results showed that most of the food groups were (less than the Recommended Daily Servings) in pre-test, then became (Equal to the Recommended Daily Servings) in post-test in the study group. While most of the food groups were (Less than the Recommended Daily Servings) in pre-test and post-test in the control group. Also, there were statistically significant differences between the study and control groups in the post-test measurements regarding the evaluation of the dietary pattern of food intake frequency at (p. value <0.05). Conclusions: The DASH system was effective in improving the dietary pattern of patients after recovery from myocardial infarction. And in assessing food intake frequency and the dietary pattern at p. value <0.05). There were statistically significant differences between the study and the control group on the post-test measures.